Spelling correctors to improve production and diffusion of linguistic knowledge - (:unkn) unknown (My University, 2005)
This article analyses the reasons of illiteracy in Subsaharian Africa and the difficulties to write african languages in an electronic format, it observes some improvement with the appearance of the Unicode standard in 1992 and It underlines the unresolved problems : lack of linguistic ressources (lexicons, descriptive grammars), lack of linguists, poor dissemination of linguistic ressources. Finally an hypothesis emerges : the presence linguistics tools (as spell correctors) on computers could help people to produce texts and to accede to linguistic knowledge.
Keywords: African Research